Academia in Transformation Scholars Facing the Arab Uprisings - Kohstall, Florian; Richter, Carola; Dhouib, Sarhan; Kastner, Fatima (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
Popular uprisings in the Middle East and North Africa (MENA) have had a deep impact, not only on the societies and political structures in the respective countries there, but also on different academic disciplines. The events that started in 2010 in Tunisia have altered academic terminology, contributed to a shift in study focus and sometimes challenged dominant theoretical approaches. The book provides an insightful and illuminating view of the transformation of the academic landscape in the aftermath of these uprisings. It analyses how the academic discourse in and on the MENA region has changed and reflects on how the aforementioned transformation processes, which are still ongoing, are shaping lines of inquiry in different disciplines, including political science, Arabic literature and language studies, philosophy, communication studies, sociology, computer studies and archaeology. The book's authors are members of the Arab-German Young Academy of Sciences and Humanities (AGYA). With contributions by Ammar Abdulrahman, Tobias Amft, Hanan Badr, Sarhan Dhouib, Kalman Graffi, Amal Grami, Maha Houssami, Christian Junge, Fatima Kastner, Florian Kohstall, Bilal Orfali, Carola Richter, Hans Jörg Sandkühler, Rana Siblini, Jan Claudius Völkel, Barbara Winckler